Stable Reference Gene Selection for qRT-PCR Normalization in Strawberry (Fragaria × ananassa) Leaves under Different Stress and Light-Quality Conditions - Yuntian Ye; Yang Lu; Guangyi Wang; Yongqiang Liu; Yunting Zhang; Haoru Tang (Horticulturae, 2021)
Selecting an appropriate reference gene is of crucial importance for improving the accuracy of qRT-PCR analyses. In this study, strawberry (Fragaria ananassa) seedlings were subjected to different environmental conditions including heat, cold, drought, salt, white-light, blue-light, and red-light treatments. The expression levels of seven candidate reference genes, including Fa18S, FaGAPDH, FaPIRUV, FaDBP, FaHISTH4, FaACTIN1, and FaACTIN2, in the strawberry leaves were measured by qRT-PCR. Then, four programs (geNorm, NormFinder, BestKeeper, and RefFinder) were employed as tools to evaluate the expression stability of the candidate reference genes. The results showed that the expression stability of the reference genes varied under different conditions. For the cold stress and white-light treatments, FaACTIN2 was evaluated to be the most stable reference gene. FaGAPDH should be used as the reference gene under salt-stress condition and red-light treatment. For the data normalization under drought-stress treatment, FaDBP is the recommended reference gene with the highest expression stability. FaHISTH4 was observed to be the best reference gene for data normalization under heat stress and blue-light treatment. This work provides information on selecting reference genes for accurate gene expression analyses of target genes in strawberry leaves under various abiotic stress and light-quality conditions.